1989
DOI: 10.1007/bf01429284
|View full text |Cite
|
Sign up to set email alerts
|

Photoionisation studies of homogeneous argon and krypton clusters using TPEPICO

Abstract: The photoionisation threshold region of homogeneous Argon and Krypton clusters Ar, and Kr, for n up to 24 formed in a free jet expansion has been studied in detail, using the threshold photoelectron photoion coincidence (TPEPICO) time of flight technique. Measurements performed at a variety of different expansion conditions (nozzle temperature and stagnation pressure) demonstrate that fragmentation of larger clusters contributes substantially to the shape of the TPEPICO spectra even for the smallest clusters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 52 publications
(71 reference statements)
4
33
0
Order By: Relevance
“…This in first place is a final state effect, as the Ar dimer cation possesses some bound states [1][2][3]. For clusters growing to about thirty atoms, from mass resolved appearance energy measurements also an influence of initial state effects was suggested [4,5]. These experiments were detailed, but did not yield insight to properties of the electronic structure beyond the position of the ionization potential (IP), or the vacuum level in a solid state terminology.…”
Section: Introductionmentioning
confidence: 99%
“…This in first place is a final state effect, as the Ar dimer cation possesses some bound states [1][2][3]. For clusters growing to about thirty atoms, from mass resolved appearance energy measurements also an influence of initial state effects was suggested [4,5]. These experiments were detailed, but did not yield insight to properties of the electronic structure beyond the position of the ionization potential (IP), or the vacuum level in a solid state terminology.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational relaxation of this ion releases about 1 eV of energy into the cluster, causing the evaporation of several groundstate atoms from the cluster, before the ion is detected in a mass spectrometer. While the initial model evoked a dimer ion core, 42 more recent experimental 20,37,38,[43][44][45] and theoretical 46 research has indicated that in Ar n ϩ cluster ions with nϽ15 the positive charge is localized in a trimer ion core.…”
Section: Discussionmentioning
confidence: 99%
“…Double excitation of the clusters is one possibility, however, the excitation of two nϭ2 excitons in the clusters would have a threshold near 27 eV, somewhat below the observed onset. Simultaneous excitation and ionization has a threshold near 28 eV, which is the sum of the excitation energy of an nϭ2 exciton and the ionization potential of the clusters ͑14.3 eV, see Ganteför et al 27 and Kamke et al 38 ͒. Double ionization has a threshold near 32 eV ͑Scheier and Mark 39 ͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, small ionic raregas clusters exhibit stronger bonding than their neutral counterparts, and the formation of ionic cores ͑dimers, trimers, etc.͒ in the ionization of clusters has been discussed. 26,27 Attempts to model the binding-energy spectrum from properties of these ionic cores were, however, less successful ͑see discussion in Ref. 9͒.…”
Section: Discussionmentioning
confidence: 99%